The formocresol technique a vital process in the management of rampant caries - Batiller, Gary M.; Serraon, Antolin P.; Jimena, Edna M. (Adviser)+.
Considered as objectives of this study are the management of primary teeth with deep carious lessions including the non-vital teeth through the formocresol technique and the evaluation of the methodology proposed by Ranly as well as the evaluation of the economic advantage in its application. Five children with rampant caries from the White Cross Institute served as samples. Pre-operative examination, radiographs taken, scaling and excavating were conducted until the medicament, formocresol was prepared and delivered into the prepared cavities. The period of the study spanned for six weeks. The technique employed was the method proposed by Ranly. A great number of Filipino children afflicted with deep carious lessions could be managed through this simple method. This is inexpensive and this can be an economic success for public health which receives a depleted budget annually.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.